GAMBARAN DUKUNGAN KELUARGA DENGAN KEPATUHAN MINUM OBAT PASIEN HALUSINASI PENDENGARAN - Pobi, Ilyas; Basmalah Harun; Rusli Abdullah; Yantimala (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2024)
Background : Auditory hallucinations are a mental disorder that is prone to recurrence. Patients with auditory hallucinations who are prone to recurrence are partly due to a lack of support from the family. Family support is to encourage patients to increase adherence to taking medication and control it at the appointed time. Purpose: to determine family support with patient medication adherence to auditory hallucinations. Case study method: The study design used in this research is a case study. The case study which is the subject of this research is used to explore the description of family support with the adherence of patients taking medication for hallucinations. Results: Table 4.3 shows that on the third day the patient was compliant in taking medication before and after receiving family support. While Table 4.3 shows that on the third day the patient was compliant in taking medication before and after receiving family support. Conclusion: Based on the results of a case study describing family support with adherence to taking medication in patients with auditory hallucinations in patients Mr.